Check Point Firewall Administration R81. 10+ : a Practical Guide to Check Point Firewall Deployment and Administration - Yakovlev, Vladimir (Packt Publishing, Limited, 2022)
Improve your organization's security posture by performing routine administration tasks flawlessly Key Features Get a gradual and practical introduction to Check Point firewalls Acquire the knowledge and skills necessary for effective firewall administration, maintenance, and troubleshooting Create and operate a lab environment with gradually increasing complexity to practice firewall administration skills Book Description Check Point firewalls are the premiere firewalls, access control, and threat prevention appliances for physical and virtual infrastructures. With Check Point's superior security, administrators can help maintain confidentiality, integrity, and the availability of their resources protected by firewalls and threat prevention devices. This hands-on guide covers everything you need to be fluent in using Check Point firewalls for your operations. This book familiarizes you with Check Point firewalls and their most common implementation scenarios, showing you how to deploy them from scratch. You will begin by following the deployment and configuration of Check Point products and advance to their administration for an organization. Once you've learned how to plan, prepare, and implement Check Point infrastructure components and grasped the fundamental principles of their operation, you'll be guided through the creation and modification of access control policies of increasing complexity, as well as the inclusion of additional features. To run your routine operations infallibly, you'll also learn how to monitor security logs and dashboards. Generating reports detailing current or historical traffic patterns and security incidents is also covered. By the end of this book, you'll have gained the knowledge necessary to implement and comfortably operate Check Point firewalls. What you will learn Understand various Check Point implementation scenarios in different infrastructure topologies Perform initial installation and configuration tasks using Web UI and the CLI Create objects of different categories and types Configure different NAT options Work with access control policies and rules Use identity awareness to create highly granular rules Operate high-availability clusters Who this book is for Whether you're new to Check Point firewalls or looking to catch up with the latest R81.10++ releases, this book is for you. Although intended for information/cybersecurity professionals with some experience in network or IT infrastructure security, IT professionals looking to shift their career focus to cybersecurity will also find this firewall book useful. Familiarity with Linux and bash scripting is a plus.